THE AIM OF RUSSIA TO DEVELOP ITS RELATIONS WITH CHINA IN 2014 - Tri Rukmana Sari (HI 16 UMY 203, 2016)
*203 This research will describe about the aim of Russia in order to developing its relations with China in 2014. Russia that has been recognize as the influence country in several aspect of diplomatic, military, economy, energy and etc. Cooperation between the Governments of Russia and China have been running after the end of the cold war to the present, and it makes a huge influence in several region especially for U.S. The attempt of Russia and China to restrain U.S Hegemony in Asia as a part of its focus to strengthen bilateral relation between Russia and China in order to dealing with U.S hegemony power throughout the U.S influence in Asia. Russia and China are continually dealing cooperation in order to balancing the U.S hegemony power in Asia. Keywords: Russia; China, U.S; Alliance partnership; Bilateral and Multilateral; Balance of Power, U.S Hegemony